Floating Currencies, SDR's and Gold Further Legal Developments. (Pamphlet Series, 1977)
This paper examines legal developments in area of floating currencies, special drawing rights, and gold in the IMF. It highlights that the breakdown of the par value system of the original Articles of the IMF and the failure of the IMF's efforts to substitute a comparable system based on central rates are producing widespread effects in international and domestic law. The floating of sterling has been an impetus to the reversal of the ancient rule that English courts can give monetary judgments only in sterling. It has also influenced the choice of the exchange rate on the day when payment is actually made.